Regeneration of Intervertebral Disc Tissue by Resorbable Cell-Free Polyglycolic Acid-Based Implants in a Rabbit Model of Disc Degeneration - Abbushi, A.; Endres, M.; Cabraja, M; Kroppenstedt, S.N; Thomale, U.W; Sittinger,M
Study Design. Different biologic strategies exist to treat degenerative disc disease. Tissue engineering approaches favor autologous chondrocyte transplantation. In our one-step-approach, a resorbable cell-free polyglycolic acid (PGA)-based implant is immersed in serum from whole blood and implanted into the disc defect directly after discectomy. Objectives. The aim of our study was to investigate the capacity of a cell-free implant composed of a PGA felt, hyaluronic acid, and serum to recruit disc cells and stimulate repair tissue formation in vivo after microdiscectomy in a rabbit model. Summary of the Background Data. Disc tissue has a limited ability to regenerate after the degeneration process was once initiated. Therefore, we developed a cellfree resorbable implant that is able to attract local cells into the defect and induce proper repair tissue formation. Methods. The cell-free implant consisting of PGA and hyaluronic acid was immersed in allogenic serum and implanted into the disc defect after discectomy in New Zealand white rabbits. One week and 6 months after the operation, the disc height index and the T2-weighted signal intensity index were determined using plane radiographs and magnetic resonance imaging. Finally, discs were explanted and investigated histologically. Animals with discectomy only served as controls. Results. In our animal studies, we could demonstrate that the T2-weighted signal intensity of the operated discs decreased in both groups 1 week after surgery. However, after 6 months, the T2-weighted signal intensity index increased by 45 percent in the implanted group whereas the index decreased further by 11 percent in the sham group. This corresponded to changes in the disc height index. Furthermore, the histologic examinations indicated cell migration into the defect and showed tissue regeneration. Conclusion. The implantation of a cell-free PGA-hyaluronic acid implant immersed in serum after discectomy induces regeneration, resulting in improvement of the disc water content and preservation of the disc height 6 months after surgery.
Keywords: DEGENERATIVE DISC DISEASE; PROTEOGLYCAN; DISCECTOMY; NUCLEUS PULPOSUS; MATRIX PROTEIN; POLYGLYCOLIC ACID; CELL-FREE IMPLANT